Hubungan Pola Hidup Terhadap Physical Wellness Pada Mahasiswa/i Fisioterapi S-1 Transfer Di Universitas Muhammadiyah Surakarta Tahun 2013 - 2014 - Nurlizan, Nurlizan; , Isnaini Herawati, S.Fis.,Ftr.,M.Sc; , Dwi Rosella K, S.Fis.,Ftr.,M.Fis (2015)
Background: Wellness is an integration of functional activities oriented to maximize the potential ability of individuals in their environment. Each individual should be able in terms of: a set pattern of life, priorities, needs and abilities of job self-development, able to interact socially in the environment. To achieve health or healthy behavior, there are seven interrelated components and dependencies that must be possessed by every social individual, they are: social wellness, physical wellness, emotional wellness, career wellness, intellectual wellness, environmental wellness, and spiritual wellness. Physical wellness is a person's ability to perform daily activities, health outcomes, maintain sufficient nutrition and ideal weight, avoid drug addiction and alcohol or cigarettes and generally positive living habits. Healthy lifestyle is a lifestyle that takes into account of the determinants of health, such as: food, exercise, and do not consume alcohol. Objective: This study aimed to determine the relationship of physical wellness lifestyle toward S1 Transfer of Physiotherapy student at the Muhammadiyah University Surakarta. Methods: This study is considered a survey research/ observation with cross sectional approach, the data distribution is not normal, the data analysis was done by using chi square test. The numbers of samples in this study were 100 students and the sampling is taken by saturated sampling, where all samples examined. Results: The data obtained are not normally distributed, statistical test done by using chi square showed that p value obtained: 0, 000 or p-value considered less than 0,05, this considered that Ha accepted, which means that there is a significant relationship between the lifestyle of the physical wellness of S1 Transfer of Physiotherapy students at Muhammadiyah University Surakarta academic year of 2013- 2014. Conclusions: There is a significant relationship between the lifestyle of the physical wellness of S1 Transfer of Physiotherapy students at Muhammadiyah University Surakarta academic year of 2013- 2014.